Baohuoside I Inhibits Tumor Angiogenesis in Multiple Myeloma via the Peroxisome Proliferator–Activated Receptor γ/Vascular Endothelial Growth Factor Signaling Pathway - Chen, Ying; Zhang, Lina; Zang, Xiaoyan; Shen, Xuxing; Li, Jianyong; Chen, Lijuan (Frontiers in Pharmacology, 2022)
Angiogenesis is associated with the progression of multiple myeloma (MM). Baohuoside I (BI) is an active mono-flavonoid with remarkable antitumor activity. Yet the impact of BI on MM-stimulated angiogenesis remains unclear. In this study, we demonstrated that BI inhibited MM-induced angiogenesis in vitro and angiogenesis in xenograft mouse model in vivo. We further showed that the PPARγ transcriptional activity was mediated by a direct physical association between BI and PPARγ. Meanwhile, the inhibition of PPARγ using lentivirus transfection of shRNA in human myeloma cell lines showed that the facilitation of PPARγ blocked angiogenesis and PPARγ repressed vascular endothelial growth factor (VEGF) transcription. Furthermore, BI treatment decreased VEGF expression, while VEGF remained unchanged after PPARγ knockdown when exposed to BI. Overall, our study reveals for the first time that BI represses MM-stimulated angiogenesis via PPARγ-VEGF signaling axis.